2019
DOI: 10.1186/s12942-019-0186-8
|View full text |Cite
|
Sign up to set email alerts
|

Using Google Earth™ and Geographical Information System data as method to delineate sample domains for an urban household surveys: the case of Maroua (Far North Region-Cameroon)

Abstract: BackgroundGetting a random household sample during a survey can be expensive and very difficult especially in urban area and non-specialist. This study aimed to test an alternative method using freely available aerial imagery.MethodsA gridded map and random selection method was used to select households for interviews. A hundred numbered of points were put along the edges of an updated map of Maroua. Then two numbers were randomly draw at a time and a line was drawn between those two numbers. A lot of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A study done by Wang et al (2017) ,and Wei et al (2018), also employed GE imaging to collect data about road and its design with certain improvisation to improve the elevation precision. A similar study also conducted by Vougat et al (2019), in Maroua-Kamerun, found that the accuracy of the object imaging until the level of imaging a house was 72%. GE app was found to be more efficient in terms of the resource and cost needed in comparison with the Global Positioning System (GPS).…”
Section: Methodsmentioning
confidence: 55%
“…A study done by Wang et al (2017) ,and Wei et al (2018), also employed GE imaging to collect data about road and its design with certain improvisation to improve the elevation precision. A similar study also conducted by Vougat et al (2019), in Maroua-Kamerun, found that the accuracy of the object imaging until the level of imaging a house was 72%. GE app was found to be more efficient in terms of the resource and cost needed in comparison with the Global Positioning System (GPS).…”
Section: Methodsmentioning
confidence: 55%
“…The population of Maroua was 403,817 in 2013 (Report of the Far North Regional Delegation of Economy, Planning, and Regional Development, 2013, not published). Geographically, the city of Maroua is located between latitude 10-13 • North of the Equator and longitude 13-15 • East of the Greenwich meridian (25).…”
Section: Study Areamentioning
confidence: 99%
“…The food consumption data used in this study were based on the existing and representative data of our previous study (6). During that study, 202 households selected using a gripped map and random selection method as described by Vougat Ngom et al (25) were surveyed. The number of households investigated was calculated and set, taking into consideration the economic feasibility of the study but also considering the results of the presurvey done in the city of Maroua.…”
Section: Data On Beef Consumptionmentioning
confidence: 99%
“…One of its significant advantages is its ability to provide geographical data at various scales, from a global perspective to a detailed street-level view, making it an ideal platform for obtaining territorial information. Additionally, Google Earth is increasingly used in education to provide an interactive and immersive learning experience on topics such as environmental science and geography [16]. UAVs can be used to navigate over a region while carrying cameras or other sensors to take high-resolution pictures or gather information such as height, temperature, or vegetation indices.…”
Section: Introductionmentioning
confidence: 99%